Vokal dalam bahasa daerah di Kalimantan Selatan: sebuah kajian tipologi bahasa - Mubarok, Ahmad; Isnendes, Retty; Kurniawan, Eri (Universitas Mulawarman, 2024)
This study aims to examine the vocal system in regional languages in South Kalimantan, focusing on eighteen varieties of local languages, namely Banjar, Sunda, Bakumpai, Lawangan, Dayak Halong, Dusun Deah, Flores, Manyan, Abal, Sasak, Javanese, Bugis, Samihin, Bajau, Madura, Berangas, Bali, and Mandar. The research method used is a qualitative descriptive approach with literature data analysis. The results showed variations in the vocal system between regional languages, with some languages having unique vowels while others showed anomalies in the distribution of vowels. The study found that the vowels /i/, /u/, /e/, and /a/ were found in all of the regional languages studied, while the vowels /ə/ were found in seventeen languages, the vowels /o/ in thirteen languages, and the vowels /ɔ/ in six languages. This research makes an important contribution to the development of language typology in South Kalimantan and can be the basis for further research on vocal anomalies in the regional language.